2019
DOI: 10.5607/en.2019.28.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Dissection of Intrinsic Optical Signal Reveals a Functional Coupling between Synaptic Activity and Astrocytic Volume Transient

Abstract: The neuronal activity-dependent change in the manner in which light is absorbed or scattered in brain tissue is called the intrinsic optical signal (IOS), and provides label-free, minimally invasive, and high spatial (~100 µm) resolution imaging for visualizing neuronal activity patterns. IOS imaging in isolated brain slices measured at an infrared wavelength (>700 nm) has recently been attributed to the changes in light scattering and transmittance due to aquaporin-4 (AQP4)-dependent astrocytic swelling. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…In a supportive role, astrocytes maintain appropriate ionic concentrations in extracellular space, for example, by taking up potassium ions (K + ) during and after intense synaptic transmission (Simard & Nedergaard, 2004;Lambert et al 2008;Dallerac et al 2013). During this process, the water molecules initially follow the movement of K + via the astrocyte-specific water channel, aquaporin-4 (AQP4), resulting in a transient volume increase in the astrocyte (Simard & Nedergaard, 2004;Andrew et al 2007;Kitaura et al 2009;Nagelhus & Ottersen, 2013;Woo et al 2018Woo et al , 2019. Then the astrocytic volume returns to normal by extruding chloride ions (Cl − ) and osmolytes, possibly via anion channels (Abdullaev et al 2006;Mulligan & MacVicar, 2006;Okada et al 2009;Woo et al 2019), followed by a subsequent water efflux through AQP4.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a supportive role, astrocytes maintain appropriate ionic concentrations in extracellular space, for example, by taking up potassium ions (K + ) during and after intense synaptic transmission (Simard & Nedergaard, 2004;Lambert et al 2008;Dallerac et al 2013). During this process, the water molecules initially follow the movement of K + via the astrocyte-specific water channel, aquaporin-4 (AQP4), resulting in a transient volume increase in the astrocyte (Simard & Nedergaard, 2004;Andrew et al 2007;Kitaura et al 2009;Nagelhus & Ottersen, 2013;Woo et al 2018Woo et al , 2019. Then the astrocytic volume returns to normal by extruding chloride ions (Cl − ) and osmolytes, possibly via anion channels (Abdullaev et al 2006;Mulligan & MacVicar, 2006;Okada et al 2009;Woo et al 2019), followed by a subsequent water efflux through AQP4.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the astrocytic K + uptake mechanism, many studies have revealed that the extracellular K + originates from the neuronal postsynaptic glutamate receptor channels that open and release during excitatory synaptic transmission (MacVicar & Hochman, 1991;Djukic et al 2007;Cheung et al 2015;Woo et al 2019). However, the exact molecular identity of the channel or transporter responsible for the K + uptake in astrocytes has not been determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative changes in reflected light intensity correspond to relative changes in the local concentrations of oxygenated hemoglobin and deoxygenated hemoglobin. OIS series of images represent a bidimensional functional map of hemodynamic signals, which are a proxy of neural activity [1]. Briefly, when a neuron fires, there is a localized consumption of oxygen revealed by an initial augmentation in deoxygenated hemoglobin.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, with larger animals, OIS needs to carry out OIS through the thinned skull with a rotative tool [3]. Can be extended to study optogenetically evoked signals, although it requires transgenic mice expressing channelrhodopsin (ChR2) [4], it can be performed in isolated brain slices ex vivo [1] or facilitated through the use of an intracranial transparent window [5]. OIS has been employed as a diagnostic tool, taking advantage of the intrinsic contrast provided by hemoglobin, which allows imaging without the addition of external contrast reagents.…”
Section: Introductionmentioning
confidence: 99%